2001
DOI: 10.3171/jns.2001.94.1.0050
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective randomized controlled trial of the efficacy of mild hypothermia for severely head injured patients with low intracranial pressure

Abstract: Mild hypothermia should not be used for the treatment of severely head injured patients with low ICP because this therapy conveys no advantage over normothermia in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
3
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(115 citation statements)
references
References 9 publications
4
103
3
5
Order By: Relevance
“…83 However, two multicenter studies have failed to show beneficial effects of hypothermia. 85,86 In infants and children, hypothermia treatment has shown preservation of oxidative defenses in the CSF after TBI. 87 A meta-analysis of the clinical trials has shown that hypothermia reduced mortality and improved neurological outcome, although this was offset with an increased risk of pneumonia.…”
Section: Clinical Studies With Hypothermiamentioning
confidence: 99%
“…83 However, two multicenter studies have failed to show beneficial effects of hypothermia. 85,86 In infants and children, hypothermia treatment has shown preservation of oxidative defenses in the CSF after TBI. 87 A meta-analysis of the clinical trials has shown that hypothermia reduced mortality and improved neurological outcome, although this was offset with an increased risk of pneumonia.…”
Section: Clinical Studies With Hypothermiamentioning
confidence: 99%
“…A higher rate of infection and worsening of coagulation have been reported in some clinical studies of hypothermia in neurotrauma [158], [159] and [160]. These complications, however, have not constituted a major problem in the majority of randomized studies [19], [20], [24] and [161], have been absent so far in ALF patients [80], [81], [119] and [120] and, importantly, they can be prevented and managed.…”
Section: Therapeutic Implicationsmentioning
confidence: 98%
“…More than 10 randomized controlled trials have not yielded consistent findings at the effects of therapeutic hypothermia in TBI [106,107]. A recent Cochrane metaanalysis evaluated the effect of hypothermia to <35°C for at least 12 consecutive hours on outcome in TBI in a total of 23 trials and 1614 patients, and concluded that there was no beneficial effect of hypothermia [108].…”
Section: Tbimentioning
confidence: 99%